Beyond Financial Metrics: Can ESG Activities Attenuate Financing Anomalies in Sharia-Indexed Firms? - Mekani Vestari; Fuad Fuad; Dwi Ratmono (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2026)
When making investment decisions, investors are increasingly taking into account environmental, social, and governance (ESG) elements as non-financial metrics, whose scores indicate a firm’s ESG-related activities. As debt financing rises, stakeholders are putting more pressure on firms to integrate ESG into their business operations. To date, various studies have provided empirical evidence concerning financing anomalies. This study aims to expand the existing literature on this topic by examining the effects of ESG on financing anomalies in non-financial firms included in the Indonesia Sharia Stock Index (ISSI) from 2018 to 2022 using panel data regression. The results confirm the existence of financing anomalies. Furthermore, ESG activities have been found to reduce financing anomalies, thereby mitigating the negative impact of debt financing on long-term stock performance. This demonstrates the moderating role of ESG on financing anomalies. Since ESG standards align with Sharia principles, the issuance of Sharia-compliant stock indices is, therefore, essential to protect investors, particularly those who adhere to these principles.